Pulsating hemorrhagic varicose veins caused by tricuspid valve regurgitation: report of a case treated by laser ablation and foam sclerotherapy - Atsushi Guntani; Sho Yamashita; Shinsuke Mii (Surgical Case Reports)
Abstract Background Varicose veins are one of the most common disease; however, secondary varicose veins caused by tricuspid valve regurgitation (TVR) are rare. Case presentation A patient who developed pulsating bleeding from superficial varicose veins due to TVR was successfully treated by endovenous laser ablation (EVLA) of the great saphenous vein (GSV) and repeated foam sclerotherapy of varicose veins. There were no complications, such as rebleeding or recanalization of the GSV during the 1-year follow-up period. Conclusions We herein report a rare case of pulsatile hemorrhagic varicose veins caused by TVR that was successfully managed by combined treatment of EVLA and foam sclerotherapy. When pulsatile varicose veins are found, the presence of TVR should be suspected.